The Roles of Telemarketing in Marketing of Marketplace at PT. LTP South Tangerang - Encep Sopandi; Nurdin; Fadli, Ahmad; Badriyah; Surya Kencana, Dadang (ASIAN PUBLISHER, 2023)
This research was conducted to determine the role of telemarketing in job marketplace marketing at PT LTP South Tangerang, the main purpose of this study was to determine the role of telemarketing in marketing the installation of job vacancy information at PT LTP South Tangerang, Telemarketing obstacles in the marketing process of installing job vacancy information, and solutions carried out to overcome obstacles that occur during the marketing process of installing job vacancy information. This research was conducted using descriptive qualitative methods, with data collection methods carried out, namely observation, interviews, and literature studies. Based on the results of the study, it can be concluded that the role of telemarketing in job marketplace marketing at PT LTP South Tangerang is to increase the number of customer databases, develop customer relationships by telephone, conduct digital marketing to increase the use and branding of job marketplaces, influence prospective customers to be interested in posting job vacancy information ads, direct and assist the process of posting job vacancy information. There are still obstacles experienced including inadequate telephone facilities, poor telephone networks, not directly connected to the target telephone recipient, and invalid database contact numbers. Then solutions were obtained to overcome existing obstacles, including solutions for inadequate telephone facilities, namely routinely cleaning the chace, preparing cellphone storage reserves and adding telephone facilities. The bad network solution is to change the provider, the solution if it is not directly connected to the target telephone recipient, namely by increasing the number of databases to be called and follow up and ask for HRD contact information so that it can be contacted directly, Then the solution to invalid contact numbers is to update the database with more relevant sources.